Psme code 1993 (Quezon City, Philippines : PSME code and standards commission, 1993)
This 1993 edition of the PSME Code is the latest step of the Society in a continuing effort to provide a comprehensive and current source of reference data on the practice of mechanical engineering in the country. It includes revisions and additions which have been approved by the Codes and Standards Commission and endorsed by the Philippine Society Mechanical Engineers.
Chapter 1 General -- Chapter 2 Commercial and Industrial Building -- Chapter 3 Power Transmission Equipment, Prime Movers, Machines and Machine Parts -- Chapter 4 Machinery Danger Zone and Points of Operation -- Chapter 6 Cranes and Other Hoisting Equipment -- Chapter 7 Boilers and Pressure Vessels -- Chapter 8 Heating, Ventilating, Refrigeration and Air-conditioning -- Chapter 9 Fire Protection -- Chapter 10 Pumps -- Chapter 11 Piping -- Chapter 12 Metrology -- Chapter 13 Machine Shop Machinery and Equipment -- Chapter 14 Manufacturing Process -- Chapter 15 Fuels and Lubricants -- Chapter 16 Materials -- Chapter 17 Instrumentations .
Keywords: MECHANICAL ENGINEERING -- LAWS